Teacher Performance Survey of Early Childhood Education in Waringin Kurung District - Anggraeni, Apriana; Yudha, Rivo Panji (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2024)
The performance of PAUD teachers has a significant impact on the quality of early childhood education. Effective teachers not only master the learning material but are also able to create a pleasant learning environment, accommodate individual children's needs, and collaborate with parents. Therefore, an in-depth understanding of the performance of PAUD teachers is a necessity to improve the quality of education at the elementary level. The research aims to describe the performance of early childhood education teachers in Waringin Kurung District. This research uses a quantitative approach because the data obtained is in numerical form and processed using descriptive research methods, then interpreted. The number of samples used was 97 PAUD teachers in Waringin Kurung District, Serang Regency. The data collection technique in this research uses a questionnaire technique which is expected to provide more accurate and specific data. The data presentation was analyzed using quantitative descriptive percentage methods to show the performance of PAUD teachers. The results of the research show that as many as 7 teachers or 7% of PAUD teachers in Waringin Kurung District are in the very good category, as many as 36 PAUD teachers or 37% have good performance, 31 PAUD teachers or 32% in Waringin Kurung District have satisfactory performance, 19 PAUD teachers or 20% have low performance, while 4 PAUD teachers or 4% in Waringin Kurung District have very low performance. The average (mean) score of respondents from the results of the research on the performance of PAUD teachers, kindergarten teachers in Waringin Kurung District, was 75.1%.